Streamlining digital signal processing : a tricks of the trade guidebook - Lyons, Richard G., 1948- (Wiley/IEEE Press, 2012)
This book presents recent advances in DSP that simplify or increase the computational speed of common signal processing operations and provides practical, real-world tips and tricks not covered in conventional DSP textbooks. It offers new implementations of digital filter design, spectrum analysis, signal generation, high-speed function approximation, and various other DSP functions. This is an ideal book for electrical engineers, computer programmers, and scientists seeking to both enhance the performance and increase the operational speed of their signal processing hardware and software. --from back cover.